Educational podcasts: A genre analysis. (July 2017) - Drew, Christopher
Academic attention to educational podcasts has grown significantly in recent years. However, to date, the concept of genres in podcasting is yet to gain scholarly attention. By examining genres emergent from a corpus of educational podcasts available online, this paper introduces the value of genre analysis to educational podcast research. It proposes three genres, named 'The Quick Burst', 'The Narrative' and 'The Chat Show'. The three genres show both the versatility of podcasting for education and how genre analysis could introduce new ideas to the educational podcasting literature, including ideas about supporting deep learning in e-learning environments.